Antibiotic use prior to seeking medical care in patients with persistent fever: a cross-sectional study in four low- and middle-income countries. (September 2021) - Ingelbeen, Brecht; Koirala, Kanika D.; Verdonck, Kristien; Barbé, Barbara; Mukendi, Déby; Thong, Phe; El Safi, Sayda; Van Duffel, Lukas; Bottieau, Emmanuel; van der Sande, Marianne A.B.; Boelaert, Marleen; Chappuis, François; et al.
Abstract: Objectives: Community-level antibiotic use contributes to antimicrobial resistance, but is rarely monitored as part of efforts to optimize antibiotic use in low- and middle-income countries (LMICs). We investigated antibiotic use in the 4 weeks before study inclusion for persistent fever. Methods: The NIDIAG-Fever (Neglected Infectious diseases DIAGnosis-Fever) study investigated aetiologies of infections in patients ≥5 years old with fever ≥1 week in six healthcare facilities in Cambodia, the Democratic Republic of the Congo (DRC), Nepal, and Sudan. In the present nested cross-sectional study, we describe prevalence and choice of antibiotics before and at study inclusion, applying the Access/Watch/Reserve (AWaRe) classification of the WHO List of Essential Medicines. Factors associated with prior antibiotic use were analysed. Results: Of 1939 participants, 428 (22.1%) reported the prior use of one or more antibiotics, ranging from 6.3% (24/382, Cambodia) to 35.5% (207/583, Nepal). Of 545 reported antibiotics, the most frequent were Watch group antibiotics (351/545, 64.4%), ranging from 23.6% (DRC) to 82.1% (Nepal). Parenteral administration ranged from 5.9% to 69.6% between study sites. Antibiotic use was most frequent among young patients (5–17 years of age; risk ratio 1.42, 95%CI 1.19–1.71) and men (RR 1.29; 95%CI 1.09–1.53). No association was found with specific symptoms. Of 555 antibiotics started before study inclusion, 275 (49.5%) were discontinued at study inclusion. Conclusions: Watch antibiotics were frequently used, and discontinued upon study inclusion. The antibiotic use frequency and choice varied importantly between LMICs. Data on local antibiotic use are essential to guide efforts to optimize antibiotic use in LMICs, should not be restricted to hospitals, and need to take local healthcare utilization into account.